Lipid and volatile dynamics shape sweet potato and honey aroma in ‘Baiye 1’ black tea - Lin Chen; Yuxuan Shi; Jingyi Pan; Yueling Zhao; Liping Liu; Qun Ye; Yuefei Wang; Zhonghua Liu; Ping Xu (Food Chemistry: X, 2025)
The albino tea cultivars represented by ‘Baiye 1’, characterized by their naturally enriched amino acid content and reduced polyphenol levels, exhibit distinctive sweet and umami flavors along with honey-like aromas, characteristics that are uncommon in traditional black teas. Nevertheless, the metabolic transformations underlying these superior sensory qualities during processing remain insufficiently understood. Here, UPLC-HRMS and HS-SPME-GC–MS/MS were employed to analyze non-volatile and volatile compounds respectively during ‘Baiye 1’ black tea (BYBT) processing. Six non-volatile compounds were identified as key taste components responsible for BYBT's sweet, umami, and mild flavors, while eight aroma-active volatiles, including β-ionone and geraniol, collectively shaped BYBT's baked sweet potato and honey-like aroma. Interestingly, lipidomics and aroma formation pathway analysis revealed that lipid transformations during rolling and drying released precursors and generated key aroma components, highlighting the pivotal role of lipid metabolism in aroma formation. Our work elucidates the flavor development mechanisms of high-amino-acid black tea and offers biochemical insights for optimizing processing and enhancing the value of specialty cultivars like ‘Baiye 1’.